Insects and Ecosystem Function - Weisser, W.W; Siemann, Evan (Ecological Studies, Analysis and Synthesis, 2008)
In the past two decades, an increasing number of ecologists have started to investigate the importance of biodiversity for ecological processes such as energy flow and nutrient cycling, often referred to as 'ecosystem functioning'. Insects are a dominant component of biodiversity in terrestrial ecosystems and play a key role in mediating the relationship between plants and ecosystem processes. This volume is the first to summarize their effects on ecosystem functioning, focusing mainly, but not exclusively, on herbivorous insects. Renowned authors with extensive experience in the field of plant-insect interactions, contribute to the volume using examples from their own work. In addition to providing concise reviews of the field, this volume discusses in detail the advantages and disadvantages of various techniques of manipulating insect herbivory. Thus, the text provides both a theoretical basis as well as practical advice for future manipulative studies of biodiversity-ecosystem functioning.